ШЕДЕВРИ МУЗИЧНОЇ ЛІТЕРАТУРИ В ЖАНРІ ПЕРЕКЛАДЕНЬ ЯК НЕВІД’ЄМНА ЧАСТИНА АКАДЕМІЧНОГО ДОМРОВОГО РЕПЕРТУАРУ (Педагогіка вищої та середньої школи, 2009)
The article considers the outstanding examples of the word musical classics, which are constantly used in pedagogical and concert practice. Nowadays the genre of settings to music expressive means, to enrich the instrument's palette with new colors and images.